Gliptins vs. Milk-derived Dipeptidyl-Peptidase IV Inhibiting Biopeptides: Physicochemical Characterization and Pharmacokinetic Profiling - Jorge Andrés Barrero (Universidad de Antioquia, 2021)
Background: Milk-derived biopeptides have reported in vitro dipeptidyl-peptidase IV (DPP-IV) inhibition, suggesting a glycemic-regulatory effect in Type 2 Diabetes Mellitus (T2DM). Nonetheless, the therapeutic application of these nutraceuticals is limited by the scarcity of knowledge regarding their pharmacokinetic profile. Objective: This study aimed to characterize and assess the pharmacokinetics of milk-derived biopeptides. Through an in silico comparative analysis with gliptins, we expected to identify enhanced properties in food-hydrolysates and suitable DPP-IV inhibiting peptides as candidates for T2DM therapy. Methods: A comparison between gliptins and biopeptides was conducted based on in silico evaluation of drug-likeness, physicochemical properties, pharmacokinetics, and synthetic accessibility. Suitable target proteins for gastrointestinal-absorbable biopeptides were determined as well. Data collection was performed on SwissADME, ADMETlab, DrugBank, SwissTargetPrediction, ChemDes, and BIOPEP-UWM platforms. Statistical analysis was carried out using a one-way ANOVA test. Results: Drug-likeness compliance showed no significant difference between gliptins and biopeptides (p>0.05) in three out of nine assessed rules, though gastrointestinal-absorbable biopeptides exhibited no significant difference with gliptins in five drug-likeness guidelines. The physicochemical evaluation revealed a significant difference (p<0.05) between both groups, with peptides exhibiting enhanced solubility, flexibility, and polarity. Nine out of thirty-six assessed biopeptides reported being likely gastrointestinal-absorbable molecules, from which six displayed ≥30% predicted bioavailability, two reported CYP450 interactions, and all were determined to be blood confined. Biopeptides showed a slightly lower clearance than gliptins yet counteracted by a significantly lower half-life. Moreover, synthetic accessibility scores indicated higher synthetic ease for biopeptides. In addition, absorbable bioactive peptides reported a considerable binding affinity to DPP-IV and Calpain-I. Conclusions: Compared to gliptins, gastrointestinal-absorbable biopeptides exhibit superior physicochemical properties (higher solubility, flexibility, and polarity), lesser CYP450 interactions, higher synthetic ease, and some reported an important affinity for DPP-IV and Calpain-I. Only a small fraction of milk-derived biopeptides are suitable drug-like compounds and feasible candidates for T2DM therapy; yet, testing their therapeutic potency remains subject to further studies.